Transportation Problem Solver for Drug Delivery in Pharmaceutical Companies using Steppingstone Method - Mallick, Chittaranjan; Bhoi, Sourav Kumar; Singh, Trailokyanath; Swain, Prachi; Ruskhan, Basheer; Hussain, Khalid; Sahoo, Kshira Sagar (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In this paper, several solutions such as initial basic feasible solution (IBFS), optimal solution and degeneracy solution of the transportation problem are given, regarding the drug delivery from drug factories to different warehouses for minimizing the delivery time as well as cost of transportation according to the destination’s requirement. In this Pandemic, it is the most essential part of the pharmaceutical marketing to focus in this cost minimization. The cost of production varies from company to company, and the transportation cost from one company drug factory to multiple warehouses also varies. Each drug factory has some specific production capacity and each warehouse has some certain amount of requirement. To verify the efficiency of this problem, we use Vogel’s method to find IBFS and compare it with the Stepping stone method for optimization of the cost. In this work, we proposed a case study related to the above problem in which the drug items to be shipped from the drug factories to the warehouses, so that the cost of the transportation is minimized. It also explains the degeneracy in the transportation techniques. From the case study, it is found that the minimum transportation cost is Rs. 212 for both techniques. However, it is observed that the Stepping stone method reduces the degeneracy better than the Vogel’s method. For scalability, we have also simulated the methods in MATLAB to observe the results in two cases. From the two cases, it is seen that Stepping stone method shows minimum cost of transportation.